(untitled) (Muitas Vozes, 2021)
This work discusses the possible functions of disconnected excerpts in essays of the Exame Nacional do Ensino Médio (ENEM). To ground our reflections, we return to the concepts of genre (BAKHTIN, 2006 [1929]; 2011 [1979]), genre format subversion (MARCUSCHI, 2008), and incoherence (KOCH; TRAVAGLIA, 2008). In the analysis, we compare the effects that the use of disconnected excerpts caused in three ENEM essays to the effects in two other genres, a petition and a blog post. We raise three possible functions for the insertion of these excerpts: that this may be an argumentative strategy, that the author reacts to the probable readers’ attention loss, and that the author tests the dialogical character of the essay. We conclude that the use of these excerpts in ENEM does not necessarily make texts incoherent, but the condition of textual production demands a greater stability of the genre’s format.